Navigating the Web3 Revolution: Regulatory Strategies for Kenya (Journal of Intellectual Property and Information Technology Law (JIPIT), 2024)
The integration of technology into daily human lives has become indispensable, shaping society and emphasizing the role of humans in the development of society. This indispensable integration is illustrated by the global rise of Web3, a decentralized application ecosystem that utilizes advanced technologies, such as crypto assets, non-fungible tokens (NFTs), decentralized finance (DeFi), decentralized autonomous organizations (DAOs), and the Metaverse. These technologies offer significant benefits alongside unique risks and challenges, necessitating innovative regulatory strategies to address them. The inherent tension between promoting innovation and safeguarding citizens’ interests requires a flexible and comprehensive regulatory framework for Web3 in Kenya, capable of adapting to the rapidly evolving technological landscape while simultaneously managing emerging risks. This research aims to identify key principles for developing effective Web3 regulations and argues for Kenya’s regulatory recognition of Web3 technologies, emphasizing potential benefits such as increased innovation, digital sovereignty, financial independence, and economic development. It also explores different regulatory strategies, such as self-regulation, co-regulation, and the implementation of co-regulatory tools like public-private dialogue (PPD). The findings propose that Kenyan regulators should adopt flexible, forward-thinking regulatory strategies that can navigate the complexities introduced by these transformative technologies.